MUHAMAD KARNO KUSUMO DARMOKO PELOPOR KARAWITAN SRAGENAN - Robert Aris Widodo (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2019)
ABSTRACT Starting from an idea to reveal the creativity of the artist who spearheaded the emergence of Karawitan Sragenan, Muhamad Karno Kusumo Darmoko through the process of artistry with the art work. Sragenan style started when the karawitan in Sragen began to be displaced by Dangdut music (orkes Melayu). Karno is one of the artists in Sragen who feel anxious about the situation and think about how to keep karawitan alive in Sragen. With the spirit of maintaining the existence of karawitan in Sragen and by having the educational background of art, Karno did some experimental process working on musical karawitan which culminate in an invention musical concept Sragenan style. Karno classifies that there are two concept of patterns in Sragenan style, they gecul and dangdut. The existence of Karawitan Sragenan style also has an impact on karawitan in Sragen, Sragen society and Muhamad Karno Kusumo Darmoko as the pioneer of Sragenan. Kata kunci : M. Karno KD, karawitan, kreativitas, Sragenan